Aggressive behavior in Lebanese University students - Sanchez-Ruiz, M.J. (2014)
Aggressive behavior (AB) among youth is a complex phenomenon that negatively affects individuals, families, and societies around the world. This study investigates the relationship between aggressive behavior (AB) and individual factors, namely trait Emotional Intelligence (trait EI), traditional personality dimensions, emotion regulation and self-worth; as well as social factors, namely accepting/rejecting parenting styles and exposure to violence. The sample consisted of 252 university students in Lebanon (154 female), with an age range of 16–30 years (M = 19.44, SD = 1.77). Results showed that Sociability (trait EI factor: social awareness, emotion management and assertiveness), openness to experience, and exposure to violence were significant positive predictors of AB, while Self-control (trait EI factor: emotion regulation, stress management and impulsiveness), conscientiousness, emotional stability and self-worth were significant negative predictors, controlling for age and gender. Implications for future research are discussed.